Elevated blood-lead levels among children living in the rural Philippines - Travis J Riddell; Orville Solon; Stella A Quimbo; Cheryl May C Tan; Elizabeth Butrick; John W Peabody (The World Health Organization, 2007)
OBJECTIVE Generally, lead poisoning is not considered a significant environmental hazard for children in rural areas of developing countries. With a prospectively designed policy experiment, the research community and the government are conducting a broad-based investigation to introduce and evaluate the impact of health policy reforms on children in a rural area of the Philippines - the Quality Improvement Demonstration Study (QIDS). As part of this study, we researched lead exposure in children under the age of five. METHODS: We sampled a population of children from the Visayas region in the central Philippines, covering approximately one third of the country's geographical area. From December 2003 to September 2004, the survey collected blood lead levels (BLL) together with demographic, socioeconomic and child health data points. Supplemental field-testing among a sub-sample of the most exposed children assessed the sources of environmental lead exposure. FINDINGS: Among children in this study, 21% (601 of 2861 children) had BLL greater than10 µg/dl. BLL were associated independently with age, haemoglobin concentration, water source, roofing material, expenditures and history of breastfeeding. A follow-up assessment of possible environmental exposures among the sub-sample of children with elevated BLL revealed no single or predominant exposure source. Instead, there appear to be multiple potential sources, such as fossil-fuel combustion, lead paint (in or around 38% of homes) and household items. CONCLUSION: Elevated BLL are common among children in the Visayas, and may signify an under-recognized threat to children living in rural areas of other developing nations. This setting has varied environmental sources of lead. Observed correlates of BLL may be of clinical, environmental and public health utility to identify and mitigate the consequences of lead toxicity.